Quinoa (chenopodium Quinoa Willd.) Flour as Novel and Safe Ingredient in Bread Formulation - Annalisa Romano; Paolo Masi; Maria Adalgisa Nicolai; Aniello Falciano; Pasquale Ferranti (Chemical Engineering Transactions, 2019)
Quinoa (Chenopodium quinoa Willd.) has a great agronomic potential across the world and its seeds and flour may represent a source of functional ingredient for novel food production, because its high protein content with all essential amino acids, absence of gluten, high dietary fiber content and abundance of natural antioxidants such as fenolic compounds. In particular, quinoa flour has been receiving an increasing attention as a substitute for wheat flour in bread formulations due to immunutritional features (Laparra and Haros, 2018). Aims of this study were to investigate the protein fraction of quinoa flour and to evaluate its in-vitro digestibility for bread formulation. The chemical composition of quinoa protein isolate and flour were investigated. Quinoa flour showed an excellent nutritional profile, including a high protein (about 14%), lipid (about 7%) and ash (about 2%) content. Proteomic and R5 ELISA analyses showed absence of gluten, confirming quinoa as a naturally gluten-free crop. The microstructure of flour and protein isolate, dough and quinoa bakery product were observed through Scanning Electron Microscopy (SEM). Furthermore, we studied the protein fraction of quinoa flour and protein isolate and to evaluate their in-vitro digestibility for a functional bread development using a static in vitro model of protein gastrointestinal digestion Romano et al. (2017). MS/MS analysis of gastrointestinal digests had a high degree of digestibility and survival of only few resistant peptides, none of which recognized by western blotting with sera of individuals allergic to cereals nor by in silico screening on allergenic sequence databases. Bakery product exclusively based on quinoa flour was prepared with valid nutritional properties. Results indicated that quinoa flour had a high degree of digestibility, supporting its excellent nutritional value and the use of quinoa as ingredient in substitutive dough formulations.